Professional Education Program for Junior High School In-Service Teachers’ Social Competence - Sitti Asriati; Syamsiarna Nappu; Nur Qalbi (STAI Hubbulwathan Duri, 2022)
Social competence is one of the competency standards that teachers must possess to be accredited as educators. With the social competence of teachers, they can communicate and associate effectively with any circle. Teacher competence is theoretically studied separately based on government law no. 14/2005 on teachers and lecturers. This research aims to determine the EFL teachers' social competence in Junior High School who followed the Professional Education Program. The sample of this study was 47 EFL teachers in the 2020-2021 academic year taken from the first and second Batches. The instrument used to collect data was closed questionnaires in the google form using the Likert scale. The collected data were then computerized and tabulated using descriptive statistics (frequency and percentage). The results showed that most EFL teachers (55%) agreed to treat students fairly and not discriminate against their parents/guardians and the school environment because of their religion, ethnicity, gender, and socioeconomic status. EFL teachers also discuss with colleagues and provide positive responses to others, can adapt well or adapt anywhere, and communicate the results of learning innovation through various media, peers, the scientific profession orally, writing, and other forms. It indicates that the Professional Education Program for In-Service Teachers contributes to the EFL teachers of junior high schools, in particular on social competence.